Muslim Feminist Hermeneutical Method to the Qur'an (Analytical Study to the Method of Amina Wadud) - Irma Riyani (Ulumuna, 2017)
Muslim feminist hermeneutical methods to the Qur’an is a response to the conservative interpretations which hegemonizes knowledge construction to shape the tradition and the methodology of the patriarchal reading of the texts. This approach demonstrates that the Qur’an is compatible with modernity and supports gender equality. This article explores one of the leading Muslim feminisit scholar, Amina Wadud, and examines her Qur’an feminist hermeneutical method. Amina Wadud is a Muslim feminist who proposes feminist hermeneutical method to interpret the Qur’an which she called ‘tawhidic paradigm.’ This article shows that Wadud’s hermeneutical approach interrogates the patriarchal reading of the Qur’anic verses that privileges one sex over another. According to her, in understanding the Qur’an three principles should be considered, namely: first, the context in which the Qur’an was revealed; second, the grammatical composition of the text; and third, the whole text, that is its weltanschauung or world-view.